Anais Do XXV Workshop De Informática Na Escola (WIE 2019) 2019
DOI: 10.5753/cbie.wie.2019.1134
|View full text |Cite
|
Sign up to set email alerts
|

Metodologias ativas para o ensino na graduação na área de Computação

Abstract: A cultura digital crescente na vida cotidiana das pessoas vem in?uenciando a forma com que os indivíduos prendem, consultam informações, participam de grupos e trocam experiências entre si. Com ela, a forma com a qual o aluno interage em sala de aula e a própria prática de ensinar também está mudando. Dessa forma, este artigo apresenta algumas metodologias ativas utilizadas em sala de aula no ensino da computação para alunos da graduação. Dentre as metodologias ativas está a Aprendizagem Baseada em Problemas e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
0
0
1
Order By: Relevance
“…Students reported that initial shyness made them more introspective during the first activities, but as the course progressed, the dynamics provided by the use of active methodologies made them overcome the initial limitations. The increase in interactions between students is similar to the reports of [45], which reinforces that the correct use of active methodologies makes students feel more motivated to carry out classroom activities.…”
Section: Discussionsupporting
confidence: 72%
“…Students reported that initial shyness made them more introspective during the first activities, but as the course progressed, the dynamics provided by the use of active methodologies made them overcome the initial limitations. The increase in interactions between students is similar to the reports of [45], which reinforces that the correct use of active methodologies makes students feel more motivated to carry out classroom activities.…”
Section: Discussionsupporting
confidence: 72%
“…Nesse contexto, as metodologias ativas (MA) surgem forma de ensinar e aprender, inclusive dentro dos cursos de ensino superior em Computação. Em [Hartwig et al 2019], afirmase que nas MA, o alunoé o protagonista do aprendizado e o professor incentiva-o a aprender e a construir seu conhecimento por meio da informação disponível. As MA abrangem diferentes maneiras de ensinar e aprender e considera-se exemplos dela, o uso da Computação Desplugada (CD) e atividades em grupo [Lázaro et al 2018].…”
Section: Introductionunclassified